Meningkatkan Motorik Halus Keterampilan Melipat KertasMelalui Penerapan Metode Demonstrasi di TK B Pertiwi Kedungwaduk 4 Kecamatan Karangmalang Sragen - UTAMI, SEFTY FAJAR TRI (2016)
Sefty Fajar Tri Utami / A 520 100 157. Education Majors Learn The Education of Age Child Early. Faculty of Teachership and Education Science, University of Muhamamdiyah Surakarta, February, 2016 This research target to know the applying of method demonstration in uplifting of fine motor skill fold the paper. Design in this research that is Research of Class Action ( Classroom Action Research). Sum up the subject in this research 15 child. Data collecting in this research is by using method of observation and documentation. Data analysed by using quantitative descriptive technique. Result of research indicate that the skill fold the paper of through/ passing method applying demonstrate in TK B of Nation Kedungwaduk 4 Subdistrict of Karangmalang Sragen obtained by a data in the early fine motor skill of skill fold the paper of equal to 28,67%, happened by the improvement of at cycle 1 equal to 42,83%, that way also at cycle 2 happened by the improvement become 63,34%, and result of cycle 3 equal to 77,8%. Inferential thereby that through method demonstration can improve the fine motor skill fold the paper of equal to 49,13% (77,8% - 28,67%).